Analysis of factors affecting the postoperative drainage in patients with abdominoplasty with circumferential liposuction - Yang, Ruomeng; Song, Zhen; Wang, Jian; Liang, Hongwei (Frontiers in Surgery, 2025)
BackgroundAbdominoplasty combined with circumferential liposuction serves as a reliable and indispensable method for aesthetic body contour. This study aims to investigate the factors that influence drainage volume and duration after the procedure.MethodsA retrospective study of 89 patients who received abdominoplasty with circumferential liposuction between January 2021 and October 2024 was conducted. Total drainage volume and duration were recorded. Univariable and multivariable linear regression and correlation analyses were utilized to identify the correlation between postoperative drainage and patient-related, and operation-related variables.ResultsThe mean total drainage volume was 420.6 ± 220.8 ml, and the mean drainage duration was 6.8 ± 1.9 days. Based on the univariate and multivariate linear regression analysis, several statistically significant associations were identified. BMI (p = 0.001), volume of lipoaspirate (p = 0.001), and weight of resected tissue (p < 0.001) were significantly associated with the drainage volume. BMI (p < 0.001), operation time (p < 0.001), volume of lipoaspirate (p < 0.001), and weight of resected tissue (p = 0.01) were risk factors influencing drainage duration.ConclusionsBMI, volume of lipoaspirate, and weight of resected tissue were associated with drainage volume and duration. Operation time was an independent factor influencing drainage duration.